Simultaneous satellite observations of IO and BrO over Antarctica - A. Schönhardt; M. Begoin; A. Richter; F. Wittrock; L. Kaleschke; J. C. Gómez Martín; J. P. Burrows (Atmospheric Chemistry and Physics, 2012)
This article reports on satellite observations of iodine monoxide (IO) and bromine monoxide (BrO). The region of interest is Antarctica in the time between spring and autumn. Both molecules, IO and BrO, are reactive halogen species and strongly influence tropospheric composition. As a result, a better understanding of their spatial distribution and temporal evolution is necessary to assess accurately their role in tropospheric chemistry. Especially in the case of IO, information on its present magnitude, spatial distribution patterns and source regions is still sparse. The present study is based on six years of SCIAMACHY (SCanning Imaging Absorption spectroMeter for Atmospheric CartograpHY) data recorded in nadir viewing geometry. Multi-year averages of monthly mean IO columns are presented and compared to the distributions of BrO. Influences of the IO air mass factor and the IO absorption cross section temperature dependence on the absolute vertical columns are discussed. The long-term observations of IO and BrO columns yield new insight into the temporal and spatial variation of IO above the Antarctic region. The occurrence of IO on Antarctic sea ice in late spring (November) is discovered and presented. In addition, the comparison between IO and BrO distributions show many differences, which argues for different mechanisms and individual nature of the release of the two halogen oxide precursors. The state of the ecosystem, in particular the changing condition of the sea ice in late spring, is used to explain the observations of the IO behaviour over Antarctica and the differences between IO and BrO distributions.